Sosialisasi Menumbuhkan Semangat Wirausahawan Kreatif Dan Inovatif Diera Digitalisasi Pada Siswa Kelas X DKV SMK 1 Pembangunan Kota Bengkulu - Putri, Tiara Renita; Soleh, Ahmad; Putra, Iswidana Utama; Wagini, Wagini; Rahman, Abdul (Jurnal Dehasen Untuk Negeri, 2024)
In the context of globalization and evolving digitalization, it is crucial for education to equip the younger generation with a creative and innovative entrepreneurial spirit. This comunity service aims to explore the impact of socialization on the development of entrepreneurial spirit among students in the 10th grade of the Visual Communication Design (DKV) program at SMK 1 Pembangunan Kota Bengkulu. Through a case study method and data collection via interviews and observations, this study highlights a significant increase in the interest and skills of young entrepreneurs after participating in socialization activities. The findings of this research can serve as a foundation for educational institutions and relevant stakeholders to strengthen socialization approaches in fostering entrepreneurial spirit among students